Pengaruh Desentralisasi Fiskal Terhadap Pertumbuhan Ekonomi Kabupaten/Kota Di Provinsi Sumatera Utara Tahun 2011-2019 - Alwi Adha Pohan; Lia Yuliana (Seminar Nasional Official Statistics, 2021)
The successful implementation of fiscal decentralization will show the achievement of public welfare by increasing economic growth. However, what happened in North Sumatera, there are indications that the public welfare has not been achieved. This can be seen from the economic growth of districts/cities which shows a slow and uneven increase. Therefore, this study aims to determine the effect of fiscal decentralization on economic growth of districts/cities in North Sumatra in 2011-2019. The analytical method used is panel data regression analysis with the fixed effects model Seemingly Unrelated Regression (SUR) method. The results showed that the PAD ratio and the DAK ratio had a positive and significant effect on economic growth of districts/cities in North Sumatra in 2011-2019. The DBH ratio and DAU ratio has no significant effect on economic growth.